Academic Status for Librarians In Nigerian University Libraries: Myth or Reality? - Onwubiko, M.C. (Ghana Library Journal, 1996)
The paper reviews the problem of academic status for University Librarians with emphasis on the situation in Nigeria. Three major problems militating against the non-recognition of librarians as academics in Nigeria are highlighted. These are lack of time for research and publication, the unwillingness on the part of the university authorities to recognise librarians as academic, and the fear of the ’publish or perish syndrome’ as academic requirement by librarians. The paper concludes that academic status for librarians in Nigerian Universities is gaining grounds.